Swift thermal reaction norm evolution in a key marine phytoplankton species. (28th February 2016) - Listmann, Luisa; LeRoch, Maxime; Schlüter, Lothar; Thomas, Mridul K.; Reusch, Thorsten B. H.
Abstract: Temperature has a profound effect on the species composition and physiology of marine phytoplankton, a polyphyletic group of microbes responsible for half of global primary production. Here, we ask whether and how thermal reaction norms in a key calcifying species, the coccolithophore Emiliania huxleyi, change as a result of 2.5 years of experimental evolution to a temperature ≈2°C below its upper thermal limit. Replicate experimental populations derived from a single genotype isolated from Norwegian coastal waters were grown at two temperatures for 2.5 years before assessing thermal responses at 6 temperatures ranging from 15 to 26°C, with pCO2 (400/1100/2200 μatm) as a fully factorial additional factor. The two selection temperatures (15°/26.3°C) led to a marked divergence of thermal reaction norms. Optimal growth temperatures were 0.7°C higher in experimental populations selected at 26.3°C than those selected at 15.0°C. An additional negative effect of high pCO2 on maximal growth rate (8% decrease relative to lowest level) was observed. Finally, the maximum persistence temperature ( T max ) differed by 1–3°C between experimental treatments, as a result of an interaction between pCO2 and the temperature selection. Taken together, we demonstrate that several attributes of thermal reaction norms in phytoplankton may change faster than the predicted progression of ocean warming.